Grittier Chinese adolescents are happier: The mediating role of mindfulness. (1st September 2018) - Li, Jingguang; Lin, Li; Zhao, Yajun; Chen, Jing; Wang, Song
Abstract: A few recent studies indicate that grit, the perseverance and passion for long-term goals, has a positive association with subjective well-being. However, less is known about the psychological mechanisms underlying this association. Here, we tested the role of mindfulness in mediating this association in Chinese adolescents who attended high schools. In Study 1 (N = 1262), we first verified the association between the grit and subjective well-being, given that this association has not been reported in the Chinese population. Consistent with the previous literature, higher levels of grit were associated with higher levels of life satisfaction, more positive affect, and less negative affect. In Study 2 (N = 627), we replicated the association between grit and subjective well-being. More importantly, mediation analyses demonstrated that the association was partly mediated by mindfulness. Together, our findings suggest that the grit may help boost adolescents' subjective well-being through their mindful mind in pursuing their long-term goals. Highlights: The link between grit and subjective well-being was tested. The grit was positively associated with subjective well-being. The association was partly mediated by mindfulness.